2008
DOI: 10.1515/znc-2008-9-1026
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cytochrome P450-2A6, -3A5 and -4B1 with Real-Time Polymerase Chain Reaction in Prostate Tissue

Abstract: Cytochrome P450 (CYP) is a heme-containing enzyme superfamily metabolizing a wide variety of xenobiotics, including drugs and carcinogens. The majority of CYP genes are expressed in the liver, however, some CYP isoforms are also reported for a number of extra hepatic tissues. We analyzed Cytochrome P450Ð2A6, -3A5 and -4B1 mRNAs using realtime reverse-transcriptase polymerase chain reaction (RT-PCR) in a total of 21 homogenized prostate tissues with or without malignancy. We detected a consistent expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was found that CYP4B1 mRNA was detected in 11 of 21 prostate cancer samples (60%) and 50% of the control samples. 15…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that CYP4B1 mRNA was detected in 11 of 21 prostate cancer samples (60%) and 50% of the control samples. 15…”
Section: Prostate Cancermentioning
confidence: 99%
“…9,10 The contribution of CYP4B1 in cancer is of particular interest as CYP4B1 gene expression was found to be altered and presumably associated with certain cancers. 7,[11][12][13][14][15][16][17] On the contrary, several studies reported that human CYP4B1 was inactive due to a loss of function substitution of proline with serine at position 427 (p.S427P). 10 Therefore, it remains dubious that the low levels of CYP4B1 have functional consequences in normal or cancerous cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gene expression analyses demonstrated the suppression of CYP4B1 in adrenocortical tumorigenesis [110]. CYP4B1 mRNA was also detected in human prostate samples [111,112]; 60% of the prostate cancer samples were positive for CYP4B1 mRNA while in non-cancerous prostate samples, only 50% were positive for CYP4B1 mRNA [112]. Similarly, CYP4B1 could also be detected in breast and tumor breast tissues, with 76.9% or 84.6%, respectively [113], thus suggesting an increased risk of developing prostate or breast cancer with increased CYP4B1 expression.…”
Section: Tissue Distribution Of Cyp4b1 Single Nucleotide Polymorphism...mentioning
confidence: 94%